THE INFLUENCE OF READING INTEREST AND SELF-EFFICACY ON READING COMPREHENSION OF THE TENTH GRADE STUDENTS AT AS-SHOFA ISLAMIC SENIOR HIGH SCHOOL PEKANBARU - Arif, Muhammad Ramadhan (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2022)
This research was aimed to investigate the influence of reading interest and self-efficacy on reading comprehension of the tenth grade students at As-Shofa Islamic Senior High School Pekanbaru. The data were collected through reading interest questionnaire, self-efficacy questionnaire and reading comprehension test. This research was correlational research design using quantitative method. The subject of the research was the tenth grade students of As-Shofa Islamic Senior High School Pekanbaru consisting 5 classes. The research sample was taken by using proportional stratified random sampling method from 5 classes which each class had different number of students. The total population was 150 students and the total sample was 50 students. Pearson’s product moment and multiple regression formula were used to analyze the data. The research findings showed that first, there was no significant influence of reading interest on students’ reading comprehension with score 0.268 > 0.05. Second, there was significant influence of self-efficacy on students’ reading comprehension with score 0.012 < 0.05. Third, there was significant influence of reading interest and self-efficacy on students’ reading comprehension with score 0.034 < 0.05 at As-Shofa Islamic Senior High School.Keyword : Reading Interest, Self-Efficacy, Reading Comprehension